Low-intensity open-field blast exposure effects on neurovascular unit ultrastructure in mice - Chao Li; Shanyan Chen; Heather R. Siedhoff; DeAna Grant; Pei Liu; Ashley Balderrama; Marcus Jackson; Amitai Zuckerman; C. Michael Greenlief; Firas Kobeissy; Kevin W. Wang; Ralph G. DePalma; et al. (Acta Neuropathologica Communications, 2023)
Abstract Mild traumatic brain injury (mTBI) induced by low-intensity blast (LIB) is a serious health problem affecting military service members and veterans. Our previous reports using a single open-field LIB mouse model showed the absence of gross microscopic damage or necrosis in the brain, while transmission electron microscopy (TEM) identified ultrastructural abnormalities of myelin sheaths, mitochondria, and synapses. The neurovascular unit (NVU), an anatomical and functional system with multiple components, is vital for the regulation of cerebral blood flow and cellular interactions. In this study, we delineated ultrastructural abnormalities affecting the NVU in mice with LIB exposure quantitatively and qualitatively. Luminal constrictive irregularities were identified at 7 days post-injury (DPI) followed by dilation at 30 DPI along with degeneration of pericytes. Quantitative proteomic analysis identified significantly altered vasomotor-related proteins at 24 h post-injury. Endothelial cell, basement membrane and astrocyte end-foot swellings, as well as vacuole formations, occurred in LIB-exposed mice, indicating cellular edema. Structural abnormalities of tight junctions and astrocyte end-foot detachment from basement membranes were also noted. These ultrastructural findings demonstrate that LIB induces multiple-component NVU damage. Prevention of NVU damage may aid in identifying therapeutic targets to mitigate the effects of primary brain blast injury.